Determinants of patient satisfaction in Asia: Evidence from systematic review of literature - Nahima Akthar; Smitha Nayak; Yogesh Pai P (Elsevier, 2023)
Background: Patient satisfaction (PS) plays a key role in enhancing healthcare outcomes and increasing the profitability of the healthcare entity. The purpose of this systematic review is to explore the antecedents of PS in Asian Countries. Methods: A systematic review of studies published between 1980 and 2021 was conducted. The search was undertaken in Scopus and Web of Science databases in December 2021. Peer-reviewed research articles published in the English language, of the Asian context, were included. Data was extracted, and the findings were narratively synthesized. Findings: A total of 43 studies were included in this review. This review has identified several determinants of PS namely, "healthcare provider-related determinants" such as organization characteristics, physical environment, technical aspects of care, service quality, interpersonal aspects of care, accessibility, affordability, waiting time, communication, and "patient-related determinants" like age, gender, education, income, socio-economic status, the patient's health status, the outcome of care, and patient experiences. Conclusion: Our review has addressed the determining factors of PS. The factors related to the health service provider and demographic characteristics of patients have an influential role on PS. However, the selected studies did not show all probable features that influence satisfaction. There is a need for more studies capturing the impact of behavioral, cultural, and socio-economic discrepancies on PS.